Assessing heterogeneity of trade-offs/synergies and values among ecosystem services in Beijing-Tianjin-Hebei urban agglomeration - Li, Qing; Li, Wenjing; Wang, Sheng; Wang, Jinfeng (Ecological indicators, 2022)
[Display omitted] •Trade-offs and synergies among the same types of ESs differed in different region.•The Multiple Ecosystem Services Landscape Index was higher in mountainous areas.•The complex relationship of different region requires different measures. Understanding the dynamic change and interrelations among multiple ecosystem services (ESs) is crucial for the sustainable development of economy and nature, especially in Beijing-Tianjin-Hebei (BTH) urban agglomeration, which is an important capital economic circle and ecological barrier in northern China. In BTH, the spatio-temporal analyses of ESs dynamics were quantified using different models, and their interrelations (i.e., trade-offs and synergies) were analyzed using the partial correlation analysis at the pixel scale. Further, a Multiple Ecosystem Services Landscape Index (MESLI) was built to discuss the integrated capacity and efficiency of ESs. The results were as follows: (1) The inter-annual variation of MESLI was significantly different in each ecological regions. The MESLI of Bashang Plateau (R-A) and Yanshan-Taihang Mountains (R-B) showed increasing trend, while decreased in Beijing-Tianjin-Xiongan Urban Agglomeration (R-C) and the agricultural region of North China Plain (R-D). Both net primary production and water conservation increased during 2000–2015, while habitat quality declined linearly, but promoted to 0.60 during 2016–2018. (2) The MESLI and single ES were high in R-B due to the high vegetation coverage, which benefited from continuous ecological engineering in this region. The low above indexes in R-C and R-D was attributed to the destruction of natural ecosystem caused by agricultural development and urban sprawl. (3) The spatial synergies among ESs were normally well in the northern Yanshan Mountain, while the trade-offs were obvious in the southern Hebei Plain, and the relationship of trade-offs and synergies among ESs in Bashang Plateaus and Beijing-Tianjin-Xiongan urban agglomeration demonstrated uniform distribution. The spatial correlation and differentiation should be considered in policy-making of regional ecosystem management.